Avaliação da crítica de Bonjour à epistemologia naturalizada de quine - Oliveira, Cínthia Roso (2009)
The project of naturalization of the epistemology proposed by Willard V. O. Quine it supplies a new way to do epistemology. Starting from that proposal, everything that is had to build knowledge on the world they are the sensitive evidences and the results obtained in the several scientific investigations, among them, the own empiric philosophical investigations. The naturalized epistemology doesn't intend to proceed of a privileged point of view in relation to the other sciences. For Quine that point of view is not possible, always originates from a world theory for since then, to reconstruct her revising and rejecting some beliefs. Starting from those conclusions of the quinean proposal it is noticed explicit rejection of the knowledge and justification a priori second which what would guarantee the beliefs ultimately on the world it would be a rational intuition given independently of the experience. Front to that, Laurence BonJour criticizes the project of naturalization of the epistemology proposed by Quine, because this proposal when not accepting a logic a priori would not be any reason to sustain, it would destroy yourself. This work tries to evaluate the critics of BonJour to the project of naturalization of the epistemology proposed by Quine. Intends to come a possible answer in the quinean project that there is not a logic a priori, but a naturalized reason developed starting from the experience that connects the sentences of the web.